Study on Decision Process and Strategy Choice Behavior under Multimode Choice - Huanmei Qin; Hongzhi Guan; Hai Yan (Discrete Dynamics in Nature and Society)
Information Display Board is used to design an experimental survey and dynamic decision process data are retrieved under a multimode choice scenario with car, bus and subway, and park and ride. It is concluded that car travelers who will switch to choosing park and ride need more decision time to compare it with the existing modes (car, bus and subway) and tend to mainly use compensatory decision strategies in the decision process. The most commonly used decision strategy for travelers is the combined strategy under the multimode choice scenario. Correlation analysis shows that the influencing factors of age, whether the travelers have ever used park and ride, and decision time highly correlate with decision strategy choice. These conclusions have a certain reference value for theory research of decision process under multimode choice.